2010
DOI: 10.1002/pssr.201004044
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the conversion efficiency of InGaN solar cells fabricated on GaN and ZnO substrates

Abstract: By the use of a device simulator that takes the quantum effect into account, we have investigated the characteristics of InGaN solar cells stacked coherently on GaN or ZnO substrates. We have found that it is necessary to fabricate non‐polar cells, N‐polar cells with p–i–n structures, or III‐polar cells with n–i–p structures in order to achieve high conversion efficiency. InGaN solar cells grown on GaN substrates and on ZnO substrates exhibit almost the same conver‐ sion efficiencies, in spite of the differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…[1][2][3] In addition, in N-polar InGaN/GaN heterostructures, the spontaneous and piezoelectric polarization directions were reversed from those in Ga-polar structures, which could be advantageous for operating green or longer-wavelength InGaN light-emitting devices and solar cells. 4,5 However, metalorganic chemical vapor deposition (MOCVD) growth of N-polar GaN on sapphire typically leads to the formation of a rough surface morphology with hexagonal pyramidal structures and lower crystalline quality than Ga-polar GaN. 6 Such hexagonal hillocks were also observed in homoepitaxial GaN layers grown on N-polar GaN bulk substrates by MOCVD.…”
mentioning
confidence: 99%
“…[1][2][3] In addition, in N-polar InGaN/GaN heterostructures, the spontaneous and piezoelectric polarization directions were reversed from those in Ga-polar structures, which could be advantageous for operating green or longer-wavelength InGaN light-emitting devices and solar cells. 4,5 However, metalorganic chemical vapor deposition (MOCVD) growth of N-polar GaN on sapphire typically leads to the formation of a rough surface morphology with hexagonal pyramidal structures and lower crystalline quality than Ga-polar GaN. 6 Such hexagonal hillocks were also observed in homoepitaxial GaN layers grown on N-polar GaN bulk substrates by MOCVD.…”
mentioning
confidence: 99%
“…The N-polar orientation (0001) has shown great promise for expanding the existing polarization engineering techniques due to the reversed direction of the spontaneous polarization field. This allows for previously unavailable techniques including improved confinement of channel electrons in N-polar HEMTs as compared to Ga-polar [5] and improved extraction of photocarriers in InGaN solar cells [6].…”
Section: Introductionmentioning
confidence: 99%
“…Such reduction in the V OC further increases with increased indium composition in the i‐InGaN layer. To overcome this issue, we propose a new device architecture composed of n‐ZnO/III‐nitride structures which does not have an adverse influence on the reduction of the V OC because its total polarization charge at the heterointerfaces is almost same as that of Ga‐polar n–i–p InGaN/GaN heterostructure proposed by Inoue et al . The use of n‐type ZnO instead of n‐GaN offers multi‐faceted advantages due to cheapness and ease of device fabrication with various nanostructures such as nanorods and nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, n‐ZnO does not have these issues since high quality n‐ZnO can be grown at lower temperature compared to that of GaN. In addition, recent simulation results by Inoue et al confirmed that the replacement of n‐GaN layer with n‐type ZnO for n–i–p InGaN/GaN solar cells did not deteriorate the device performance.…”
Section: Introductionmentioning
confidence: 99%